PRODUCT REVIEW METHODOLOGY FROM THE PHARMACEUTICAL MARKET - Elena V. Kiryushkina; Inna A. Kostrikina (Измерение, мониторинг, управление, контроль, 2023)
Background. The relevance of the proposed methodology for recalling substandard products from the pharmaceutical market is determined by the requirements of GOST R ISO 9001-2015 and GOST R ISO 10393-2014. The aim of the work is to choose methods for identifying poor-quality products in the pharmaceutical market and develop a procedure for recalling them. Materials and methods. To solve this problem, the method of the matrix of consequences and probabilities was used according to the indicators "risk probability" and "risk impact level". Results. In the course of the work, a methodology was proposed for recalling poor-quality products from the pharmaceutical market, which is an integral part of the quality management system for pharmaceutical products. Conclusions. The positive results of the work open up the prospect of effective application of the methodology as a basis for organizing the recall management process in any pharmaceutical industry or for improving an existing process.